Bridge floor geopolymer concrete material and preparation method thereof
By using polymer concrete for bridge decks and replacing cement with industrial waste, the problems of long construction time and environmental pollution of bridge decks have been solved, achieving rapid setting and high strength of bridge deck paving, thus improving construction efficiency and environmental friendliness.
Patent Information
- Application Number
- CN202311132801.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-05
- Publication Date
- 2025-03-07
AI Technical Summary
Existing bridge deck paving materials suffer from problems such as long construction time, high resource consumption, and serious environmental pollution, especially the large consumption of cement, which leads to resource scarcity and environmental pollution.
The bridge deck uses polymer concrete material, which uses industrial waste such as silica fume, mineral powder, water glass, and MgO to replace cement, and is combined with polypropylene fiber. It is mixed in a specific ratio and then quickly set and hardened to meet the construction requirements of steel-concrete composite bridge deck.
It shortens construction time, improves early strength, reduces the risk of cracking, reduces cement usage, protects the environment, conforms to environmental protection principles, and enhances the safety performance and durability of the bridge deck.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete materials for rigid pavement, and mainly relates to a bridge deck geopolymer concrete material and a preparation method thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Steel-concrete composite bridge deck is a composite bridge deck composed of concrete and steel bridge deck connected by shear nails. Compared with steel bridges, composite bridges can save a certain amount of steel, alleviate fatigue problems, reduce the disadvantages of easy corrosion of steel structures and lower maintenance costs during operation. Compared with concrete bridges, composite bridges have the advantages of light weight, lower manufacturing costs, and shorter construction time.
[0004] With the continuous advancement of bridge engineering construction in my country, the demand for concrete is also increasing, which has led to the current situation of huge cement consumption and resource scarcity in my country, and the production of cement will cause dust and other harmful substances. Geopolymer concrete uses mineral powder and silica fume to completely replace cement, which can not only save the use of cement and reduce environmental pollution, but also reuse industrial waste, which is in line with the environmentally friendly concept advocated by my country. The extensive promotion of alkali-activated UHPC engineering applications can make an important contribution to my country's goal of reaching carbon peak in 2030. Summary of the invention
[0005] The purpose of the present invention is to provide a bridge deck geopolymer concrete material and a preparation method thereof. The bridge deck geopolymer concrete has a mechanical strength equivalent to that of bridge deck cement concrete, can shorten the construction time, has a fast coagulation and hardening speed, and develops early strength quickly. Adding MgO can reduce the early age shrinkage of the bridge deck geopolymer concrete. Moreover, the cementitious material is made of industrial waste, which can reduce the consumption of cement and reduce the harm to the environment. The bridge deck geopolymer concrete is suitable for large-scale promotion and application on steel-concrete composite bridge decks.
[0006] In order to achieve the above technical objectives, the present invention adopts the following technical solutions: A bridge deck geopolymer concrete material is composed of the following raw materials in parts by weight: 140-160 parts of silica fume, 210-230 parts of mineral powder, 80-100 parts of water glass, 14-18 parts of NaOH, 18-26 parts of MgO, 95-115 parts of water, 380-400 parts of sand, 900-920 parts of gravel, and 19-27 parts of polypropylene fiber; the water-to-binder ratio of the concrete material is 0.24-0.33.
[0007] Preferably, the sand is composed of sand of the following particle sizes: 185 to 205 parts of sand with an average particle size of 0.5 to 1 mm, 107 to 127 parts of sand with an average particle size of 0.25 to 0.5 mm, and 68 to 88 parts of sand with an average particle size of 0.125 to 0.25 mm; Preferably, the stones are composed of stones of the following particle sizes: 354 to 374 parts of stones with an average particle size of 5 to 10 mm, and 536 to 556 parts of stones with an average particle size of 10 to 20 mm.
[0008] Preferably, the bridge deck geopolymer concrete material is composed of the following raw materials in parts by weight: 145-155 parts of silica fume, 215-225 parts of mineral powder, 85-95 parts of water glass, 15-17 parts of NaOH, 20-24 parts of MgO, 100-110 parts of water, 385-395 parts of sand, 905-915 parts of gravel, and 21-25 parts of polypropylene fiber; the water-cement ratio of the concrete material is 0.26-0.31.
[0009] Preferably, the sand is composed of sand of the following particle sizes: 190 to 200 parts of sand with an average particle size of 0.5 to 1 mm, 112 to 122 parts of sand with an average particle size of 0.25 to 0.5 mm; 73 to 83 parts of sand with an average particle size of 0.125 to 0.25 mm; Preferably, the stones are composed of stones of the following particle sizes: 359 to 369 parts of stones with an average particle size of 5 to 10 mm; 541 to 551 parts of stones with an average particle size of 10 to 20 mm.
[0010] Preferably, the concrete material is composed of the following raw materials in parts by weight: 150 parts of silica fume, 220 parts of mineral powder, 90 parts of water glass, 16 parts of NaOH, 22 parts of MgO, 105 parts of water, 390 parts of sand, 910 parts of gravel, and 23 parts of polypropylene fiber; the water-cement ratio of the concrete material is 0.28.
[0011] Preferably, the sand is composed of sand of the following particle sizes: 195 parts of sand with an average particle size of 0.5 to 1 mm, 117 parts of sand with an average particle size of 0.25 to 0.5 mm, and 78 parts of sand with an average particle size of 0.125 to 0.25 mm; The stones are composed of stones with the following particle sizes: 364 parts of stones with an average particle size of 5 to 10 mm, and 546 parts of stones with an average particle size of 10 to 20 mm.
[0012] Preferably, the polypropylene fiber density is 0.91 g / cm 3 The modulus of the water glass sodium silicate solution is 2.1 to 2.3.
[0013] In view of the current research on bridge deck paving materials at home and abroad, the present invention has developed a bridge deck geopolymer concrete material which can shorten the construction time, meet the engineering quality standards and is environmentally friendly.
[0014] A method for preparing the bridge deck geopolymer concrete material as claimed in claim 1, comprising the following steps: (1) Evenly mixing sand, gravel, mineral powder, silica fume and MgO to obtain a first mixture; (2) adding water to the first mixed material prepared in step (1) and mixing them evenly to obtain a second mixed material; (3) adding water glass sodium silicate into the second mixed material prepared in step (2), mixing them evenly, to obtain a third mixed material; (4) The polypropylene fibers are evenly added into the third mixture prepared in step (3), and the mixture is evenly mixed to obtain a bridge deck geopolymer concrete material.
[0015] The third aspect of the present invention provides the use of the above-mentioned bridge deck geopolymer concrete material in bridge construction.
[0016] Due to the fast solidification and hardening characteristics of geopolymer concrete materials, the bridge deck geopolymer concrete material should be quickly poured onto the steel bridge deck and vibrated using engineering equipment until no bubbles appear on the surface. The surface is then smoothed and steam-cured for 28 days using a bridge steam engine.
[0017] The beneficial effects of the present invention are: (1) The fluidity of a bridge deck geopolymer concrete material involved in the technical solution of the present invention is about 170 mm, showing excellent fluidity, reducing the construction difficulty of steel bridge deck concrete paving materials.
[0018] (2) The technical solution of the present invention involves a bridge deck geopolymer concrete material, which has a 28-day compressive strength of up to 60 MPa, a flexural strength of up to 7.5 MPa, and an elastic modulus of up to 30 MPa. It has good mechanical properties and can greatly improve the safety performance of steel bridges. The addition of MgO can reduce the cracking risk of steel bridge deck concrete paving materials, meeting the requirements of the "Design Code for Steel-Concrete Composite Bridges".
[0019] (3) The technical solution of the present invention involves a bridge deck geopolymer concrete material, in which the cementitious material adopts industrial waste materials such as mineral powder and silica fume, thereby reducing the use of cement, thereby saving energy and protecting the environment.
[0020] (4) The present invention does not use cement in the mix design, and uses mineral powder and silica fume industrial waste slag instead of cement, so that the industrial waste slag can be reused and energy is saved.
[0021] (5) The present invention adds MgO as a shrinkage reducer in the mix design. Because geopolymer concrete has the characteristic of high shrinkage at an early age, in order to reduce the risk of cracking, MgO is added to achieve the purpose of shrinkage reduction, and the engineering quality is higher. DETAILED DESCRIPTION
[0022] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0023] In some embodiments, the gravel is a combination of various particle sizes of 5-10mm and 10-20mm. In the present invention, the combination of gravel with various particle sizes can form a more uniform bridge deck geopolymer concrete structure, thereby enhancing the stability of the bridge deck pavement. The combination of gravel with various particle sizes forms a high-density structure, which can also increase the compressive resistance of the paved surface.
[0024] In some embodiments, the sand is a combination of various particle sizes of 0.5-1mm, 0.25-0.5mm, and 0.125-0.25mm. In the present invention, since the bridge deck geopolymer concrete shrinks greatly at an early age, the combination of sands with various particle sizes can reduce its shrinkage performance, reduce cracking of the bridge deck geopolymer concrete caused by drying or temperature changes, and improve the durability of the project. The combination of sands with various particle sizes can also improve the fluidity of the bridge deck geopolymer concrete, making it easier to construct and pour, improve the work efficiency of workers, and reduce construction costs.
[0025] In some embodiments, the admixture is mineral powder and silica fume. Such admixture can reduce the porosity inside the bridge deck geopolymer concrete, reduce water penetration and erosion by harmful substances such as carbon dioxide and sulfate, and improve the durability of concrete such as antifreeze, anti-seepage, and anti-corrosion. Fine powders such as mineral powder and silica fume are active, and their high early activity can promote the early strength development and hardening speed of concrete. At the same time, fine powders such as mineral powder and silica fume are cheaper than cement, and can replace the use of cement to reduce engineering costs.
[0026] In some embodiments, the added fiber is polypropylene fiber, which can improve the durability, crack resistance and impact resistance of bridge deck geopolymer concrete. Polypropylene fiber can effectively control the crack expansion in bridge deck geopolymer concrete, improve tensile strength and tensile strength, reduce the deformation of bridge deck geopolymer concrete, and thus reduce the response of bridge deck geopolymer concrete to load. At the same time, polypropylene fiber can also increase the impact resistance of bridge deck geopolymer concrete, enhance the seismic resistance of bridge deck geopolymer concrete, and can effectively reduce the losses caused by natural disasters such as earthquakes. In addition, bridge deck geopolymer concrete with the addition of polypropylene fiber can also effectively prevent water seepage and oil seepage, improve the durability of bridge deck geopolymer concrete, and extend the service life of bridge deck geopolymer concrete.
[0027] In some embodiments, the MgO can be used as an alkaline substance adsorbent to reduce the alkaline substance content in the bridge deck geopolymer concrete and improve the performance of the concrete. MgO can provide additional CaO, thereby promoting the formation of dibasic sulfate in the bridge deck geopolymer concrete, thereby achieving hardening and strength improvement of the concrete. MgO can also reduce the water absorption of concrete, improve the durability of concrete, resist chloride corrosion, sulfate corrosion, etc., thereby extending the service life of concrete. In addition, MgO, as a mineral admixture, has a good compensating shrinkage effect on the bridge deck geopolymer concrete.
[0028] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0029] The embodiments described in the present invention are all prepared by the following method: The present invention also provides a method for preparing a bridge deck geopolymer concrete material, which is prepared according to the following steps: S1 Calculate the amount of each raw material according to the mix ratio of the bridge deck geopolymer concrete material, put all the gravel, sand, mineral powder, silica fume and MgO into the mixer and stir for 2 minutes; S2 adds water to the mixture obtained in S1 and stirs for 2 minutes; S3: adding sodium silicate water glass to the mixture obtained in S2 and stirring for 2 minutes; S4 adds polypropylene fiber to the mixture obtained in S3 and stirs for 2 minutes to obtain a bridge deck geopolymer concrete material with a fluidity of about 170 mm; S5 pours the bridge deck geopolymer concrete material prepared in S4 onto the steel bridge deck, and vibrates it for 60 seconds with a vibrating rod or vibrator until no bubbles appear on the surface, smoothes the surface, and uses a water-retaining curing film to maintain moisture retention at room temperature for 28 days.
[0030] Implementation Case 1 A bridge deck alkali-activated geopolymer material comprises the following raw materials in parts by weight: 195 parts of sand with an average particle size of 0.5 to 1 mm; 117 parts of sand with an average particle size of 0.25 to 0.5 mm; 78 parts of sand with an average particle size of 0.125 to 0.25 mm; 354 parts of gravel with an average particle size of 5 to 10 mm; 536 parts of gravel with an average particle size of 10 to 20 mm; 150 parts of silica fume; 220 parts of mineral powder; 90 parts of water glass sodium silicate solution with a modulus of 2.2; NaOH 16 parts; MgO 22 parts; 105 parts of water; 23 parts of polypropylene fiber; The water-to-binder ratio of the alkali-activated geopolymer material for the bridge deck is 0.28.
[0031] Implementation Case 2 A bridge deck alkali-activated geopolymer material comprises the following raw materials in parts by weight: 185 parts of sand with an average particle size of 0.5 to 1 mm; 107 parts of sand with an average particle size of 0.25 to 0.5 mm; 68 parts of sand with an average particle size of 0.125 to 0.25 mm; 364 parts of gravel with an average particle size of 5 to 10 mm; 546 parts of gravel with an average particle size of 10 to 20 mm; 140 parts of silica fume; 210 parts of mineral powder; 80 parts of water glass sodium silicate solution with a modulus of 2.2; NaOH 14 parts; MgO 18 parts; 115 parts of water; Polypropylene fiber 19 parts; The water-to-binder ratio of the alkali-activated geopolymer material for the bridge deck is 0.33.
[0032] Implementation Case 3 A bridge deck alkali-activated geopolymer material comprises the following raw materials in parts by weight: 205 parts of sand with an average particle size of 0.5 to 1 mm; 127 parts of sand with an average particle size of 0.25 to 0.5 mm; 88 parts of sand with an average particle size of 0.125 to 0.25 mm; 374 parts of gravel with an average particle size of 5 to 10 mm; 556 parts of gravel with an average particle size of 10 to 20 mm; Silica fume 160 parts; 230 parts of mineral powder; 100 parts of water glass sodium silicate solution with a modulus of 2.2; NaOH 18 parts; MgO 26 parts; 95 parts of water; Polypropylene fiber 27 parts; The water-to-binder ratio of the bridge deck alkali-activated geopolymer material is 0.24.
[0033] The compressive strength, flexural strength and elastic modulus tests were conducted on the standard specimens prepared from the bridge deck geopolymer concrete material described in Implementation Cases 1-3 after 28 days of standard curing. The experimental data are shown in Table 1: Table 1 Bridge deck geopolymer concrete material test data project Compressive strength (MPa) Flexural strength (MPa) Elastic modulus (GPa) Implementation Case 1 60 7.5 30 Implementation Case 2 55 6.1 24 Implementation Case 3 67 8.3 35 From Table 1, it can be seen that the compressive strength of implementation case 1 of the present invention can reach 60 MPa, the flexural strength can reach 7.5 MPa, and the elastic modulus can reach 30 GPa. The compressive strength of implementation case 2 can reach 55 MPa, the flexural strength can reach 6.1 MPa, and the elastic modulus can reach 24 GPa. The compressive strength of implementation case 3 can reach 67 MPa, the flexural strength can reach 8.3 MPa, and the elastic modulus can reach 35 GPa, indicating that it has good mechanical properties.
[0034] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of them with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A bridge deck geopolymer concrete material, characterized in that: The concrete material is composed of the following raw materials in parts by weight: 140-160 parts of silica fume, 210-230 parts of mineral powder, 80-100 parts of water glass, 14-18 parts of NaOH, 18-26 parts of MgO, 95-115 parts of water, 380-400 parts of sand, 900-920 parts of gravel, and 19-27 parts of polypropylene fiber; the water-to-binder ratio of the concrete material is 0.24-0.
33.
2. The bridge deck geopolymer concrete material according to claim 1, characterized in that: The sand is composed of sands of the following particle sizes: 185 to 205 parts of sands with an average particle size of 0.5 to 1 mm, 107 to 127 parts of sands with an average particle size of 0.25 to 0.5 mm, and 68 to 88 parts of sands with an average particle size of 0.125 to 0.25 mm; The stones are composed of stones with the following particle sizes: 354 to 374 parts of stones with an average particle size of 5 to 10 mm, and 536 to 556 parts of stones with an average particle size of 10 to 20 mm.
3. The bridge deck geopolymer concrete material according to claim 1, characterized in that: The concrete material is composed of the following raw materials in parts by weight: 145-155 parts of silica fume, 215-225 parts of mineral powder, 85-95 parts of water glass, 15-17 parts of NaOH, 20-24 parts of MgO, 100-110 parts of water, 385-395 parts of sand, 905-915 parts of gravel, and 21-25 parts of polypropylene fiber; the water-cement ratio of the concrete material is 0.26-0.
31.
4. The bridge deck geopolymer concrete material according to claim 3, characterized in that: The sand is composed of sands of the following particle sizes: 190 to 200 parts of sands with an average particle size of 0.5 to 1 mm, 112 to 122 parts of sands with an average particle size of 0.25 to 0.5 mm, and 73 to 83 parts of sands with an average particle size of 0.125 to 0.25 mm. The stones are composed of stones with the following particle sizes: 359 to 369 parts of stones with an average particle size of 5 to 10 mm; and 541 to 551 parts of stones with an average particle size of 10 to 20 mm.
5. The bridge deck geopolymer concrete material according to claim 1, characterized in that: The concrete material is composed of the following raw materials in parts by weight: 150 parts of silica fume, 220 parts of mineral powder, 90 parts of water glass, 16 parts of NaOH, 22 parts of MgO, 105 parts of water, 390 parts of sand, 910 parts of gravel, and 23 parts of polypropylene fiber; the water-cement ratio of the concrete material is 0.
28.
6. The bridge deck geopolymer concrete material according to claim 5, characterized in that: The sand is composed of sand of the following particle sizes: 195 parts of sand with an average particle size of 0.5 to 1 mm, 117 parts of sand with an average particle size of 0.25 to 0.5 mm, and 78 parts of sand with an average particle size of 0.125 to 0.25 mm; The stones are composed of stones with the following particle sizes: 364 parts of stones with an average particle size of 5 to 10 mm, and 546 parts of stones with an average particle size of 10 to 20 mm.
7. The bridge deck geopolymer concrete material according to claim 1, characterized in that: The polypropylene fiber density is 0.91 g / cm 3 The modulus of the water glass sodium silicate solution is 2.1 to 2.
3.
8. A method for preparing the bridge deck geopolymer concrete material according to any one of claims 1 to 7, characterized in that: Use the following steps: (1) Evenly mixing sand, gravel, mineral powder, silica fume and MgO to obtain a first mixture; (2) adding water to the first mixed material prepared in step (1) and mixing them evenly to obtain a second mixed material; (3) adding water glass sodium silicate into the second mixed material prepared in step (2), mixing them evenly, to obtain a third mixed material; (4) The polypropylene fibers are evenly added into the third mixture prepared in step (3), and the mixture is evenly mixed to obtain a bridge deck geopolymer concrete material.
9. Use of the bridge deck geopolymer concrete material according to any one of claims 1 to 7 and / or the bridge deck geopolymer concrete material prepared by the preparation method according to claim 8 in bridge construction.
10. The use according to claim 9, characterized in that: The bridge deck geopolymer concrete material is poured onto the steel bridge deck, vibrated until no bubbles appear on the surface, smoothed, and steam cured for 28 days.